Optically Defined Reconfigurable THz Metasurfaces using Graphene on Iron‐Doped Lithium Niobate. Issue 12 (30th October 2022) - Gorecki, Jon; Noual, Adnane; Mailis, Sakellaris; Apostolopoulos, Vasilis; Papasimakis, Nikitas
Abstract : Graphene plasmonic devices have been demonstrated to show great potential for reconfigurable metasurfaces due to the tuneable electronic charge transport properties of graphene in response to electrostatic gating. Iron‐doped lithium niobate is proposed as a platform for patterning‐free optically reconfigurable graphene metasurfaces in the THz spectral region. Under structured illumination, the lithium niobate undergoes charge migration in the bulk, where carriers migrate away from illuminated regions, forming spatially patterned charge distributions capable of electrostatic tuning of graphene. These charge distributions are stable in the dark, however, can be redefined by subsequent illumination. Through the use of numerical simulations, it is demonstrated that optically defined charge distributions in lithium niobate can tune locally the graphene Fermi level allowing for plasmonic resonances at THz frequencies. Abstract : A rewriteable platform for optically defined plasmonic structures is investigated based on graphene on iron‐doped lithium niobate, with a view to creating adaptive plasmonic devices.